Quantitative comparisons and models of time-averaging in bivalve and brachiopod shell accumulations - Krause, Richard A.; Barbour, Susan L.; Kowalewski, Michai; Kaufman, Darrell S.; Romanek, Christopher S.; Simões, Marcello Guimarães [UNESP]; Wehmiller, John F. (Paleontological Soc Inc, 2010)
The variation in time-averaging between different types of marine skeletal accumulations within a depositional system is not well understood. Here we provide quantitative data on the magnitude of time-averaging and the age structure of the sub-fossil record of two species with divergent physical and ecological characteristics, the brachiopod Bouchardia rosea and the bivalve Semele casali. Material was collected from two sites on a mixed carbonate-siliciclastic shelf off the coast of Brazil where both species are dominant components of the local fauna.Individual shells (n = 178) were dated using amino acid racemization (aspartic acid) calibrated with 24 AMS radiocarbon dates. Shell ages range from modern to 8118 years B.P. for brachiopods, and modern to 4437 years for bivalves. Significant differences in the shape and central tendency of age-frequency distributions are apparent between each sample. Such differences in time-averaging magnitude confirm the assumption that taphonomic processes are subject to stochastic variation at all spatial and temporal scales. Despite these differences, each sample is temporally incomplete at centennial resolution and three of the four samples have similar right-skewed age-frequency distributions. Simulations of temporal completeness indicate that samples of both species from the shallow site are consistent with a more strongly right-skewed and less-complete age-frequency distribution than those from the deep site.We conclude that intrinsic characteristics of each species exert less control on the time-averaging signature of these samples than do extrinsic factors such as variation in rates of sedimentation and taphonomic destruction. This suggests that brachiopod-dominated and bivalve-dominated shell accumulations may be more similar in temporal resolution than previously thought, and that the temporal resolution of multi-taxic shell accumulations may depend more on site-to-site differences than on the intrinsic properties of the constituent organisms.